Students as researchers: the effects of employing law students on an empirical research project. Issue 2 (3rd April 2022) - Dickinson, Jill; Ferris, Katy; Marson, James
ABSTRACT: Given the increasingly competitive higher education (HE) marketplace, it is becoming progressively more important for university law schools to distinguish their offer. In England and Wales, it is commonplace for non-law undergraduate degree programmes to incorporate compulsory empirical research training within discrete modules or as part of a broader research skills package. Yet this element is typically missing from traditional LLB programmes. Addressing the gap in the literature around HE students' perceptions of conducting empirical research, in this paper we explore insights into the benefits of or barriers to undertaking such research and the extent to which students believe that it should form part of their undergraduate experience. This paper is based on findings from a small-scale, pilot case study at a post-1992 higher education institution (HEI) involving students who participated in an extracurricular empirical research evaluation project. The findings reveal perceived benefits for three key stakeholder groups: students as researchers, the host HEI and the local community where the research took place. Drawing on these themes, we conclude by offering recommendations for law schools to learn from their counterparts in other disciplines and explore potential opportunities for incorporating empirically based research training within law undergraduate degree programmes.